2016
DOI: 10.5624/isd.2016.46.4.239
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian young dental practitioners' use and acceptance of digital radiographic examinations

Abstract: PurposeThe aim of this study was to investigate the use and acceptance of digital radiographic examinations by Brazilian dental practitioners in daily practice and to evaluate the advances that have occurred over the past 5 years.Materials and MethodsDental practitioners enrolled in extension courses at the Piracicaba Dental School, University of Campinas, Brazil, responded to a self-administered questionnaire in the years 2011 and 2015. They were asked about sociodemographic factors and their knowledge and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
(24 reference statements)
2
12
1
2
Order By: Relevance
“…[3][4][5][6][7][8] Brightness and contrast adjustment tools are among the most used image enhancement features during radiographic evaluations performed in scientific research and clinical practice. 9,10 While several studies have allowed the observers to use the brightness and contrast tools freely during the evaluation of digital radiographic images, 4,[11][12][13][14] only one previous study evaluated the interference of these tools in the diagnosis of caries lesions. 15 However, in that study published in 1998, the levels of brightness and contrast were not limited nor controlled, and the radiographic system used is currently outdated.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Brightness and contrast adjustment tools are among the most used image enhancement features during radiographic evaluations performed in scientific research and clinical practice. 9,10 While several studies have allowed the observers to use the brightness and contrast tools freely during the evaluation of digital radiographic images, 4,[11][12][13][14] only one previous study evaluated the interference of these tools in the diagnosis of caries lesions. 15 However, in that study published in 1998, the levels of brightness and contrast were not limited nor controlled, and the radiographic system used is currently outdated.…”
mentioning
confidence: 99%
“…In fact, panoramic radiography is not recommended for the diagnosis of soft tissue calcifications due to the inherent The image enhancement can be achieved by using postprocessing enhancement tools, such as brightness and contrast, available in imaging software applications (Rovaris et al, 2016). The use of digital radiographs includes benefits for the patients because image quality can be slightly improved when exposure factors are not optimum, eliminating the need for repetition and, thus, reducing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement in digital image systems and software has increased the possibility of image enhancement and diagnostic task‐specific postprocessing adjustments to improve image quality (Sabarudin & Tiau, ). Among the adjustments available, brightness and contrast are greatly used by radiologists for scientific research purposes and by dentists in clinical practice (Rovaris et al, ). In general, such image enhancement can be adjusted according to the examiner's subjective judgment on image quality (Kamburoğlu, Barenboim, & Kaffe, ).…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in the United Kingdom found that 49% of general dental practitioners in the study used digital intraoral radiography in 2011 1 . In Brazil, the percentage of participating young dental practitioners using digital radiography increased significantly from 55.6% in 2011 to 85.4% in 2015 2 . A more recent study conducted in 2018 found that 98% of responding dentists in Sweden had made the transition to digital radiography, with only 2% still using the film technique 3 …”
mentioning
confidence: 94%